CT Anatomical Features and Dimensions of the Rabbit Adrenal Glands - Kamelia Stamatova-Yovcheva; Rosen Dimitrov; Diyana Vladova; David Yovchev; Hristo Hristov; Vladi Nedev; Nikolay Goranov; Avche Dineva (Veterinary Sciences)
Background: Adrenal glands are situated cranially and in close proximity to both kidneys. The rabbit is a preferred animal pet species and is also used as an experimental model in research. The aim of this study was to investigate the CT anatomical features of the rabbit adrenal glands, using the CT device SOMATOM. Methods: Ten sexually mature clinically healthy rabbits, with body weights from 2.5 to 3.0 kg were used. They were separated into two groups—five males and five females. CT algorithm: Transverse, sagittal, and dorsal CT studies were performed. The animals were positioned in supine recumbency. They were anesthetized with 15 mg/kg Zoletil® 50. Helical CT was carried out. The body was scanned from the intrathoracic part of the abdominal cavity to the pelvic inlet. CCD, DVD, and MLD dimensions were measured. Results: Transverse CT scans at the Th12 and L1 level visualized the topography of the right and left adrenal glands. Sagittal CT scans of Regio abdominis, 10 mm to the right and to the left of the median plane, showed the right and left adrenal glands as findings with intermediate attenuation. The dorsal CT investigation of Regio abdominis 30 mm and 45 mm ventral to the spine demonstrated both glands in the vicinity of abdominal organs and large blood vessels. CCD of the right adrenal gland was 6.9 ± 0.5 mm, DVD of the same gland was 5.7 ± 0.7 mm, and MLD was—3.9 ± 0.3 mm. CCD of the left adrenal gland was 5.4 ± 0.6 mm, DVD was—4.0 ± 1.1 mm, and MLD was—4.1 ± 0.9 mm. Conclusions: CCD and DVD of the right adrenal gland were greater than the same parameters of the left gland. MLD of the right adrenal gland was lower than the same parameter measured for the left one.